(3SbW GdRfOs - (3GdJfhNj GdeYQj, CHh GdYdGA, TjN GdeYQI, CMeO Hf YHO Gddg Hf SdjeGf, J(B449(3g`s ((3CHh HcQ Hf jhSa GdHdGWjs)
(3ChdgG (B:s
(3CeG HYO aEf GdTYQGA cCaQGS JJGHYf aj eOi eG bUQ efgG hbO cfJ aj ReGf GdMOGKI bGd CHh GdYdGA aj ePgH GdeOjM hde jcf ef WdGH GdQaO, hGdhRf ef GdhGaQ hGdbGajs
(3BNQgG (B:s
(3CQGc aj GdCQV SjGQ Edi TQa (B*** (3ceG THjgc aj GdBaGb SjGQ , cCfc GdHOQ hGdOfjG efGRdg (B*** (3aeG jdjbc EdG djdI GdOGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 157s
(3eYLe GdeDdajf(B: 1 / 181s
(3cTa GdXfhf(B: 2 / 992s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs